Building Bridges Between Education and Health Care in Canada: How the ICF and Universal Design for Learning Frameworks Mutually Support Inclusion of Children With Special Needs in School Settings - Tomas, Vanessa; Cross, Andrea; Campbell, Wenonah N. (Frontiers in Education, 2018)
Since the 1990s, educators have prioritized inclusion of students with disabilities in general educational settings. Concurrently, healthcare professionals (HCPs) have recognized the need to support students’ academic functioning and participation at school. Despite this recognition, integration of health support services in schools remains a significant challenge and the extent to which students with special needs fully participate at school is often less than optimal. In this paper, we suggest that combining health and education conceptual frameworks would advance the goal of inclusion by enhancing inter-professional communication and collaboration. The World Health Organization’s International Classification of Functioning, Disability and Health (ICF) is a health framework that focuses on functioning and participation via a lens of inclusivity, universality, and a holistic approach to health and disability. Similarly, Universal Design for Learning (UDL) is an educational framework for guiding the design of instructional materials, methods, and assessments to be inclusive and accessible for all. Both frameworks are well-established in their respective fields, but have yet to “cross the border” to influence each discipline’s practices. While researchers have alluded to the potential utilization of both frameworks in education settings, there is limited guidance on how these two frameworks may be combined in practice. In this paper, we will compare the ICF and UDL frameworks, and provide insight into how utilization of both frameworks may enhance inter-professional collaboration and support inclusion in school settings.